Entrelaçando artes: Frevo, Ala Ursa e processos de criação em dança na escola - Sales, Hayala César de (2020)
“Interweaving arts: Frevo, Ala Ursa and dance creation processes at school” is a Master's research from the Professional Master's Program in Arts from the Federal University of Paraíba, supervised by professor Dr. Carolina Dias Laranjeira. The research developed a process of creation in dance at school in order to change the ways of relating art and popular cultures in the educational context, contributing to a rupture in the ways of learning, making and appreciating art, inspired by the traditional knowledge of Frevo dance and the Ala Ursa game. For that, it has the participant research as main method, being developed in the classroom, in the field of the studied dances and with the students of a class of the final years of the first stage of Elementary School (years 1-5) of the Municipal School Padre Leonel da Franca, located in the neighborhood of Ernesto Geisel, in João Pessoa - PB.